Multifunctional π‐Conjugated Additives for Halide Perovskite. Issue 17 (22nd March 2022) - Lao, Yinan; Yang, Shuang; Yu, Wenjin; Guo, Haoqing; Zou, Yu; Chen, Zhijian; Xiao, Lixin
Abstract: Additive is a conventional way to enhance halide perovskite active layer performance in multiaspects. Among them, π ‐conjugated molecules have significantly special influence on halide perovskite due to the superior electrical conductivity, rigidity property, and good planarity of π ‐electrons. In particular, π ‐conjugated additives usually have stronger interaction with halide perovskites. Therefore, they help with higher charge mobility and longer device lifetime compared with alkyl‐based molecules. In this review, the detailed effect of conjugated molecules is discussed in the following parts: defect passivation, lattice orientation guidance, crystallization assistance, energy level rearrangement, and stability improvement. Meanwhile, the roles of conjugated ligands played in low‐dimensional perovskite devices are summarized. This review gives an in‐depth discussion about how conjugated molecules interact with halide perovskites, which may help understand the improved performance mechanism of perovskite device with π ‐conjugated additives. It is expected that π ‐conjugated organic additives for halide perovskites can provide unprecedented opportunities for the future improvement of perovskite devices. Abstract : π ‐Conjugated additives are competitive for halide perovskite devices. In 3D perovskite, π ‐electrons with ordered molecular arrangement and distinct interfacial dipole moment can bond with [PbI6 ] 4− octahedral to passivate defects and guide crystallization. As for low‐dimensional case, perovskites with π ‐conjugated ligands exhibit high conductivity and narrow band gap, therefore, charge transfer is greatly promoted.